Common interface to remotely control video cameras from different vendors - Vahtera, Teemu (fi=Turun yliopisto|en=University of Turku|, 2018)
Nowadays, there are dozens of different video camera manufacturers and countless models. Some of these vendors have controlling methods to control the cameras from a distance. Even an average user probably owns cameras from different vendors and thus might also have two different controlling schemes at hand. This thesis is based on an assumption that two different camera controlling methods can be used together with an integration solution. The target audience is those who have a need to use cameras from different vendors and are interested in synchronizing the controlling for easier post production. The thesis presents a review on some camera vendors and their wireless remote control applications at referenced time. The selected vendors, Panasonic and GoPro, and research environment setup of a KALI2.0 and Windows7 virtual machines with two WiFi adapters are introduced. The first part of the thesis’ empirical study focuses on solving the Panasonic Image App controlling protocol by exploring the contents of a Android application package. Final output is a way to control the Panasonic camera with a list of recognized commands and an emulation script for Panasonic Image App. The second part of the empirical study presents the investigation and solving of GoPro RC controlling scheme. The functionality of both a GoPro RC and a camera are researched through WiFi traffic analysis and then emulated. The study provides emulation scripts for both the RC and the camera to validate the discovered controlling scheme. When the controlling schemes of both cameras are understood and the emulation scripts are created, an integration solution is created. The solution is a proof of a concept in a form of a Python script with the help of two different WiFi-adapters. In addition, the thesis details some further work and describes few ways how the proof of concept solution could be made more complete and utilized further. Also an possible issue of security of the controlling schemes is introduced.